2022
DOI: 10.1016/j.heliyon.2021.e08711
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and workload as predictors of satisfaction with life in Peruvian female university professors with a family burden

Abstract: Psychological distress and workload as predictors of satisfaction with life in Peruvian female university professors with a family burden, HELIYON, https://doi.org/10.1016/ j.heliyon.2021.e08711. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
7
0
4
Order By: Relevance
“…Similar finding was reported in a study involving frontline nurses exposed to excessive workload due to the pandemic and the higher risk of adverse mental health disorder due to the COVID-19 pandemic. [52] Esteban et al [53] also found in their study that workload significantly influences psychological distress and satisfaction with life among female Peruvian university professors who are also housewives. This implies that to mitigate mental health disorder, stress, burnout, and anxiety, efforts have to be channeled to moderating the impact of workload on employees for efficient output in the workplace.…”
Section: Discussionmentioning
confidence: 95%
“…Similar finding was reported in a study involving frontline nurses exposed to excessive workload due to the pandemic and the higher risk of adverse mental health disorder due to the COVID-19 pandemic. [52] Esteban et al [53] also found in their study that workload significantly influences psychological distress and satisfaction with life among female Peruvian university professors who are also housewives. This implies that to mitigate mental health disorder, stress, burnout, and anxiety, efforts have to be channeled to moderating the impact of workload on employees for efficient output in the workplace.…”
Section: Discussionmentioning
confidence: 95%
“…The review in Table 1 indicates that 21 studies show the linkage between job demand on mental health among academicians in higher education. Most of studies reviewed are related to job demand in the context of the higher education institutions from a quantitative perspective (Teixeira, Marqueze & Moreno, 2020;Zhang et al, 2022;Brondino et al, 2022;Springer et al, 2023;Damayanti et al, 2020;Alwaely & Jarrah, 2020;Awang et al, 2021;Akunne et al, 2021;Kabito et al, 2020;Hussin et al, 2022;Jonge & Huter, 2021;Anees et al, 2021;Isa & Palpanadan, 2020;Mohamed et al, 2021;Shen & Slater, 2021;Adebayo, 2022;Nasution et al, 2022;Esteban et al, 2022;Almhdawi et al, 2021;Liu & Yan, 2020).…”
Section: The Influence Of Job Demand On Mental Healthmentioning
confidence: 99%
“…Some of the studies argued that academic staff with high workloads negatively affect their well-being (Shen & Slater, 2021: Zhang et al, 2022. Furthermore, studies show that academicians in higher education institutions have a high stress level (Hussin et al, 2021;Kabito et al, 2020;Esteban et al, 2022;Almdawi et al, 2021). Moreover, academicians in South Africa (Naidoo-Chetty & du Plessis, 2021) and China (Zhang et al, 2022) revealed that challenges encountered in the academic setting were caused by job demands such as unfavorable working circumstances, restricted opportunities for career advancement, elevated levels of work overload, and inadequate resources.…”
Section: The Influence Of Job Demand On Mental Healthmentioning
confidence: 99%
“…Tingkat kejadian distres pada mereka lebih tinggi dibandingkan dengan yang tidak merasakan penambahan beban kerja dengan kejadian distres tertinggi terdapat pada sub-kelompok informal (89.6%). Pada penelitian yang dilakukan pada wanita yang bekerja sebagai profesor di Peru didapatkan hubungan yang positif antara beban kerja dan distres psikologis dan kedua hal tersebut dapat memengaruhi secara negatif terhadap kepuasan hidup (Carranza Esteban et al, 2022).…”
Section: Perilaku Pencegahan Dan Distres Psikologisunclassified